Oil and politics in Latin America nationalist movements and state companies - Philip, George 1951- (Cambridge Latin American studies, 1982)
This book provides a study of the transformation of the Latin American oil system from one in which the international oil companies dominated to one which is dominated by the main state oil companies, and an account of how some of the more important of the state companies have operated. This comprehensive guide to the evolution of the Latin American oil system combines in one volume a synthesis of material from secondary sources and original research and thus provides an invaluable reference for all concerned with the history and economy of Latin America and with the development and functioning of the international oil industry